Marketing Strategy Bagi Sociopreneurship: Extended Brand Melalui Penggunaan E-commerce Dalam Meningkatkan Brand Preference - Amelia, Amelia; Ronald, Ronald; Sucipto, Hadi (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2022)
Sociopreneurs by using a local values ​​approach are expected to further encourage RT to take risks for better family life by involving the underprivileged and marginalized. Another Way Towards Independent and Prosperous (Jalin Matra) which is one of the focuses of the Government East Java as a form of support for Sociopreneur by the Governor of East Java in 2014 with a poverty reduction agenda. Therefore, it is important for Mrs RT to know about the use of online media to market products. So, this research must also start by knowing the effect of brand offering, internet shopping experience, word of mouth, brand familiarity, brand evaluation on brand preference so that appropriate advice can be given regarding the appropriate use of online media for the products offered. The number of samples used in this study was 100 respondents. This study uses software called SPSS version 22.0 in managing data and analyzing data. This study has six hypotheses and five hypotheses are accepted and one hypothesis is rejected.